THE EFFECTIVENESS OF SCRIPTED AND IMPROVISED ROLE-PLAY IN DEVELOPING SPEAKING SKILLS: CLASSROOM ACTION RESEARCH - Maya Marsevani; Mustafa, Diba Yuri; Nugraha, Hendra (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
This study aimed to investigate how structured drama activities supported by iterative teaching and peer evaluation could enhance learners’ pronunciation, fluency, and confidence in speaking English. This Classroom Action Research (CAR) was conducted to enhance the English-speaking abilities of tenth-grade students at one school in Batam through drama-based instruction. The study involved 44 students from Grade 10, who were selected based on document analysis indicating poor performance in speaking-related tasks. A systematic approach was utilized, which included a pre-test, two cycles of implementation, and a post-test. The pre-test results revealed that 59% of students were at Level 1 and 27% at Level 2, indicating serious deficiencies in pronunciation, fluency, and self-confidence. After the intervention, 100% of the students (n = 44) advanced to Level 3, representing a complete elimination of Level 1 and Level 2 classifications and a 52-point increase in average speaking scores (from M = 38.7 to M = 90.6). This improvement was achieved through structured drama activities such as monologues, role-plays, and improvisational skits supported by warm-up exercises, peer evaluation, and iterative teaching modifications. The findings confirm that drama is not only an effective practice-based strategy but also a theoretically grounded pedagogy aligned with Vygotsky’s Sociocultural Theory and Krashen’s Affective Filter Hypothesis, as it creates low-anxiety, interactive learning environments that facilitate authentic communication. The study contributes to both theory and pedagogy by demonstrating how scripted and improvised role-play can systematically transform learners’ oral proficiency in EFL classrooms while offering a replicable framework for adaptive, reflective language teaching.